Population Dynamics of Indian Mole Rat, Bandicota bengalensis during Different Growth Stages of Paddy and Wheat Crops in Punjab - Kaur, Kajalpreet; Singh, Rajwinder (International Journal of Bio-resource and Stress Management, 2019)
The study was carried out in the fields of village Dhatt, District Ludhiana (Punjab, India) (Ludhiana 30.91°N, 75.85’E). There was pre-dominance of Bandicota bengalensis over other rodent species like Mus booduga and Tatera indica. Total number of live burrow count recorded was maximum during tillering stage and minimum during panicle initiation and dough stages, respectively in both crops. In paddy crop, as the total number of B. bengalensis burrows decreases from tillering to pre-harvesting stage there is rise and fall in trap index of B. bengalensis but during lean period there is rise in trap index due to increase in B. bengalensis burrows due to increase in population build up of this species (mean trap index 8.82). In wheat crop, total number of B. bengalensis burrows remain almost same from tillering to lean period stages except dough stage and there is rise and fall in trap index of B. bengalensis which was maximum during dough stage and then decreases at pre-harvesting stage and again rises in lean period (mean trap index 7.42). The percentage cut tillers and damage (kg acre-1) recorded in paddy and wheat crops were 0.28, 0.46 and 7.93, 11.76, respectively. During panicle initiation, dough and pre-harvesting stages, sex ratio was in favour of females while it was in favour of males in tillering stage, whereas it was vice versa for wheat crop. So, control measures should be done at panicle initiation stage in paddy crop and tillering stage in wheat crop to manage B. bengalensis and its damage.